Histopathological spectrum of central nervous system lesions - Joshi, Himanshu; Awasthi, Seema; Dutta, Shyamoli; Bhardwaj, Rashmi (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Central nervous system (CNS) neoplasms, in India, constitute 1.9% of all cancers and in U.S. adults - 2% of all cancers. Many of the non-neoplastic CNS lesions can clinically & radiologically simulate brain tumours. In such cases, histopathological examination (HPE) can be helpful in differentiating between neoplastic and non-neoplastic etiologies. Materials and Methods: This retrospective descriptive study of histopathological analysis of brain tumours was carried out in TMMC&RC, Department of Pathology from January 2015 to December 2018. The biopsies were processed by routine histological techniques and H&E stained sections were analyzed. Special stains and IHC were performed wherever appropriate. The diagnosed brain tumours were classified according to WHO 2016 classification system. Results: A total of 96 CNS biopsies were studied. The neoplasms constituted 62 (64.6%) cases, which included 60 (96.8%) primary, 1 (1.6%) metastatic and 1 miscellaneous lesion (1.6%). The 3 most common primary tumours were Astrocytic tumours, Schwannomas and Meningiomas. About 34(35.4%) cases were non neoplastic out of which the 2 most common lesions were: Cystic Lesions and non-specific inflammation. Patients’ age ranged from 5 days to 80 years. The ratio of number of male and female patients was 1:1.67. IHC for Glial Fibrillary Acidic Protein (GFAP) was positive in astrocytomas and mixed neuronal-glial tumours. Conclusion: The present study provides information regarding the spectrum and frequency of various CNS lesions in our area and concludes that histological examination of biopsies is gold standard for accurate diagnosis of various lesions of CNS when coupled with radiological and clinical data.